Wireless real-time punching force measurement and landing location capture boxing scoring system - Puntipunyanon, S.; Senakham, T.; Lorpipatana, B. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This article was to disclose an objective boxing scoring system by capturing punching force and landing location wirelessly to augment subjective judgment official AlBA scoring system for scoring blow decision. A FlexiForce sensor was embedded at the scoring knuckle part in each closed boxing glove with a battery-powered microcontroller with wireless communication. Head guard and body guard padding were embedded with tactile switches located at legitimated landing locations with microcontrollers. A ringside computer was used to capture signals from gloves, head guards and body guards of both boxers in competition for real-time punching force and landing location information processing for scoring judgment. The system was demonstrated as proposal towards AlBA President and executive committees during 2008 Olympic Qualifying Round in Bangkok.